The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/2396987319883160
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of stroke across Europe: A population-based cost analysis

Abstract: Introduction: In 2017, 1.5 million people were diagnosed with stroke, 9 million were living with stroke and 0.4 million died because of stroke in 32 European countries. We estimate the economic burden of stroke across these countries in 2017. Patients and methods: In a population-based cost analysis, we evaluated the cost of stroke. We estimated overall health and social care costs from expenditure on care in the primary, outpatient, emergency, inpatient and nursing/ residential care settings, and pharmaceutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
172
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(179 citation statements)
references
References 19 publications
2
172
0
5
Order By: Relevance
“…The healthcare burden of stroke in European Union (EU) was approximately €20 billion in 2015, and €27 billion in 2017. In 2015, almost 72% of these expenses were represented by hospital care [7], and in 2017 a decrease of the percentage was observed; only 45% of the expanses were incurred by healthcare systems [8]. The results of the studies revealed that the costs regarding stroke (health and social care costs) / capita are associated with increases in a nation's wealth, resulting in increased stroke-related costs [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The healthcare burden of stroke in European Union (EU) was approximately €20 billion in 2015, and €27 billion in 2017. In 2015, almost 72% of these expenses were represented by hospital care [7], and in 2017 a decrease of the percentage was observed; only 45% of the expanses were incurred by healthcare systems [8]. The results of the studies revealed that the costs regarding stroke (health and social care costs) / capita are associated with increases in a nation's wealth, resulting in increased stroke-related costs [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, almost 72% of these expenses were represented by hospital care [7], and in 2017 a decrease of the percentage was observed; only 45% of the expanses were incurred by healthcare systems [8]. The results of the studies revealed that the costs regarding stroke (health and social care costs) / capita are associated with increases in a nation's wealth, resulting in increased stroke-related costs [7,8]. Also, large variations in health and social care expenses for stroke have been indicated, even for those countries with similar levels of national income [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stroke is the most frequent cause of permanent disability in adults and one of the most important causes of death [1]. Over the next years, global stroke burden is expected to increase steadily, mainly because of population aging [2]. Ischemic stroke remains to represent more than 80% of all strokes.…”
Section: Introductionmentioning
confidence: 99%